(untitled) (KYAMC Journal, 2017)
Background: Menopausal symptoms in postmenopausal women is a health hazard all over the world. Physical exercise may play a significant role in the management of menopausal symptoms among postmenopausal women. Objective: This study was undertaken to see the effects of physical exercise on menopausal symptoms among postmenopausal women. Methodology: This study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka, from 1st January, 2009 to 31st December, 2009. A total number of 60 postmenopausal women having age ranged from 50-60 years were included in the study. Among 60 postmenopausal women, 30 were performing regular physical exercise and 30 were sedentary postmenopausal women. History of menopausal symptoms from postmenopausal women were collected from known relatives and associates. The statistical analysis was done by using appropriate test as applicable. Results: Menopausal symptoms were significantly (p<0.001) higher in sedentary postmenopausal women than postmenopausal women with regular physical exercise. Conclusion: Physical exercise could be effective in improving menopausal symptoms in postmenopausal women. KYAMC Journal Vol. 5, No.-2, Jan 2015, Page 514-518